Development of Integrated Thematic Learning Models in Primary School Education - Faqih Hakim Hasibuan; Sri Minda Murni; Abdurrahman Adisaputera (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Abstract: This study aims to describe the level of student activity in the learning process of the integrated thematic learning model and how the level of validity of the integrated thematic learning model. Learning that is carried out with separate subjects will cause less development of children to think holistically and make it difficult for students to relate concepts to their real life everyday. This research was conducted at SD N 101788 and SD N 101789 Marindal I, Patumbak District. Research is carried out through research and development or in English Research and Development is a research method used to produce certain products, and to test the effectiveness of certain products Thematic learning in elementary schools is a relatively new thing, so that its implementation is not as expected. . It can be concluded that integrated thematic learning is that students are given the opportunity to investigate various strategies and ways they believe are in accordance with their abilities to collaborate on problems. This model emphasizes the process of fully student involvement to be able to find the material they are learning and relate it to real life situations so as to encourage students to be able to apply it in student life. Keywords: Model Development; Integrated Thematic; Primary school